Effect of pasteurization and Sa-tay marinade on quality changes in oyster (Crassostrea belcheri) meat - Boonprasop, Saree; Siripongvutikorn, Sunisa; Sutthirak, Pornpong; Pimpa, Benchamaporn (Journal of Food Technology Research, 2025)
The combination of pasteurization and Sa-tay marination represents a practical and applicable strategy for enhancing the microbial safety, sensory quality, and shelf life of oysters, thereby supporting both public health and the seafood industry. This study aimed to investigate the effects of pasteurization and Sa-tay marination on quality changes in oyster meat after inoculation with test pathogenic bacteria. Results showed that pasteurization at 80oC for 8 minutes completely eliminated an initial inoculum of pathogenic bacteria (108 CFU/g), including Escherichia coli, Salmonella Typhimurium, Vibrio cholerae, V. parahaemolyticus, and V. vulnificus. The combination of pasteurization and Sa-tay marination effectively eliminated E. coli, S. Typhimurium, V. cholerae, V. parahaemolyticus, and V. vulnificus in oyster meat. However, the total volatile base (TVB) value slightly increased after 9 and 12 days of storage. In contrast, trimethylamine nitrogen (TMA-N) was not detected. In summary, pasteurization is a highly effective method for reducing pathogenic bacteria in oyster meat. Without inoculation with pathogenic bacteria, oyster meat marinated with Sa-tay showed improved safety, resulting in lower microbial counts. When combined with Sa-tay marination, this approach also supports extended shelf life. This technique offers a practical solution for seafood processors aiming to improve product safety and commercial viability.